(untitled) (Fiep Bulletin - online, 2014)
Assessment of cardiovascular risk factors and physical activity (compulsory physical education (Pe) and extra-curriculum sport activities) in secondary school children followed by education in effective lifestyle measures. Participation in compulsory physical education was studied in 760 students (295 boys, 465 girls), age 15-18 years of 55 secondary schools, residents of bratislava, were studied in years 2011-2013. Participation in extra-curricular sports activities was studied in subgroup of 211 children (119 boys, 92 girls). We measured anthropometric parameters and blood pressure and tested physical ability by ruffi er test. We found out by ruffi er test that students regularly participating in compulsory Pe are more physically fi t (p=0.012). students spending more hours per day at the computer are physically less fi t (p=0.02). We found out that smoking students avoid compulsory Pe twice than students - non-smokers. the number of smoking girls is 1.2 times higher than the number of smoking boys. for other indicators, a statistically signifi cant difference was not confi rmed, but more favorable results in blood pressure, weight and bmi were shown for regularly participating students at the compulsory Pe. We found out that there is relationship between level of education of mother and children´s participation in extra-curricular sports activities (p=0.027). We confi rmed that the ruffi er test of extra-curricular sports active children testifi ed better physical ability (p=0.048). We demonstrated relationship between regular nutrition and bmi values (p=0.016). because of physical activity children feel their life more interesting and fulfi lled. compulsory Pe and in the same way extra-curricular sports activities of secondary school children have positive impact on cardiovascular risk factors. negative habits (avoid the Pe and smoking) of lifestyle in young people often multiply. qualifi ed professional teachers of Pe and as well parents play key role in creation of positive attitude towards physical activities in children.